Polymyxin B Loosens Lipopolysaccharide Bilayer but Stiffens Phospholipid Bilayer - Fu, Lei (Biophys J, 2020)
Multidrug-resistant Gram-negative bacteria have increased the prevalence of a variety of serious diseases in modern times. Polymyxins are used as the last-line therapeutic options for the treatment of infections. However, the mechanism of action of polymyxins remains in dispute. In this work, we used a coarse-grained molecular dynamics simulation to investigate the mechanism of the cationic antimicrobial peptide polymyxin B (PmB) interacting with both the inner and outer membrane models of bacteria. Our results show that the binding of PmB disturbs the outer membrane by displacing the counterions, decreasing the orientation order of the lipopolysaccharide tail, and creating more lipopolysaccharide packing defects. Upon binding onto the inner membrane, in contrast to the traditional killing mechanism that antimicrobial peptides usually use to induce holes in the membrane, PmBs do not permeabilize the inner membrane but stiffen it by filling up the lipid packing defect, increasing the lipid tail order and the membrane bending rigidity as well as restricting the lipid diffusion. PmBs also mediate intermembrane contact and adhesion. These joint effects suggest that PmBs deprive the biological activity of Gram-negative bacteria by sterilizing the cell.